CyberWalk (2006)
CyberWalk follows a holistic approach covering science, technology and applications to best realize the visionary goal of enabling quasi-natural unconstrained omni-directional walking in virtual environments. We plan to develop a unique high-fidelity multimodal platform - named CyberCarpet - on which people can freely walk in any direction. Throughout the project we will put the CyberWalk developments on a solid, human-centred footing. At the end of CyberWalk, the ability to experience a physical walkthrough in an extended virtual environment will showcase the achievements of the project. For this we here exploit an archaeological site. However, this application will only be a case in point for the wide range of applications that the CyberCarpet will offer, including entertainment, rehabilitation, training, sports, and architecture.